BIOETIKA PENELITIAN BIOEKOLOGI TUMBUHAN POHON KELAPA DI PANTAI KURANJI, KABUPATEN LOMBOK BARAT - Ratna Ariyanti; Sulistia Febriani; Slamet Mardiyanto Rahayu (LPPM, Akademi Administrasi Rumah Sakit Mataram, 2025)
This study aims to examine the application of bioethical principles in the bioecological study of coconut plants (Cocos nucifera) at Kuranji Beach, West Lombok Regency. Coastal ecosystems play an important role in maintaining environmental balance, protecting shorelines from abrasion, and supporting biodiversity as well as the livelihoods of coastal communities. The research methods used include field observations and descriptive analysis of ecosystem conditions and plant interactions with their surrounding environment. The results show that coconut plants have a significant ecological role in maintaining the stability of coastal ecosystems, while also providing economic benefits to local communities. However, increasing human activities pose potential threats to environmental sustainability, making the application of bioethical principles essential in research practices. A bioethical approach can minimize negative impacts and support ecosystem sustainability. Therefore, the integration of bioethics in bioecological research is crucial to ensure that scientific activities are conducted in a responsible and sustainable manner.